A Paleontological Approach to the Antithetical and Opposite Concepts in the Holy Quran - Reza Mohammadi; Mohammadi Jafar Asgari (دراسات في اللغة العربيّة وآدابها)
The Arabic concepts of Tebaq, Tazzad, Momathela, or Moqabela (comparison, antithesis, contrast) refer to a kind of literary or aesthetic device in Arabic rhetoric which juxtaposes two concepts, at two opposite poles, with each other. Concepts such as light and darkness, day and night, beginning and end, overt and covert are examples of contrast. However, the present study expresses a different viewpoint towards the issue of Tebaq or Antithesis in the Holy Quran. The basic claim of the present study is founded on the paleontological approach. Paleontology, like archeology, tries to excavate the foundations of concepts by getting to the depth of thoughts and ideas through the ages and centuries. The concept of Tebaq or binary oppositions constitutes the basis of eastern and western thoughts and is the governing spirit in Eastern Yin and Yang and some Western sciences such as psychology, philosophy, and literary criticism are founded on Tebaq or Antithesis. In addition, this binary view can be seen in the Holy Quran, but afer a careful analysis of this holy book, we can discern that the Quranic view toward binaries is totally different from those of western and eastern philosophers and scholars. An accurate analysis of Quranic concepts reveals three types of Tebaq: moderate Tebaq, synonymous Tebaq, and monotheistic Tebaq. The important issue which the present article is to emphasize is that Eastern and Western civilizations are founded on moderate binaries, while the foundations Quranic civilizations are based on monotheistic Tebaq. Accordingly, the present study is to investigate the Tebaq method in the Holy Quran from a paleontological point of view. The researchers in this study claim that social engineering based on monotheistic Tebaq is an important and valuable measure which can help the development of Quranic human sciences.